Dosis de compost de residuos orgánicos en el desarrollo agronómico de Lycopersicum esculentum L. tomate variedad Rio Grande. Loreto, 2024 - Rios Acuy, Arturo Alejandro (2025)
This study was carried out on land in the Zungarococha Estate-San Juan Bautista District, where the effect of different doses of organic waste compost (10, 20, 30 and 40 t/ha) on the growth and yield of the Rio Grande tomato variety was evaluated. The results showed a positive correlation between the compost doses and the parameters evaluated. A significant increase in agronomic characteristics was observed, as well as fruit weight/ha With the increase in compost per ha in the treatments, the most favorable results of the study were in T4 (40 t). The trial concludes that compost from organic waste is a promising tool to improve tomato productivity in Loreto, contributing to a more sustainable agriculture. Additional studies are recommended to optimize compost doses, evaluate fruit quality, and interaction with other crop management factors.